Three new species of Cleradini from Australia (Hemiptera: Heteroptera: Rhyparochromidae) - Malipatil, M. B.; Blacket, M. J. (Zootaxa, 2011)
Neoclerada parainsulicola sp. nov., Paramahisa kununurraensis sp. nov., and Laticlerada tasmanica sp. nov., have been described and illustrated. Cleradini are generally found in tropical habitats; the first two new species are described from tropical northern Australia, whereas the last species is the first record of Cleradini for cool temperate Tasmania.